Assessing Knowledge, Attitudes, and Practices (KAP) Towards the One Health Approach in Governmental Officers in Egypt - Elsersawy, Nour (AUC Knowledge Fountain, 2026)
Background: the one health (OH) approach emphasizes the interconnectedness among human, animal, and environmental health and requires multisectoral collaboration to address complex health challenges. Egypt faces significant threats at the human-animal-environment interface, including endemic and emerging zoonotic diseases, antimicrobial resistance (AMR), food safety challenges, and vector-borne diseases. Despite established coordination mechanisms and the launch of the One Health National strategic framework (2023-2027) of Egypt, the extent to which oh principles are understood, embraced, and practiced by governmental officers responsible for implementation remains incompletely understood. Objectives: this study assessed and evaluated the knowledge, attitudes, and practices (KAP) regarding the one health approach in governmental officers from Egypt’s Ministry of Health and Population (MoHP), Ministry of Agriculture (MoAL), and Ministry of Environment (MoE), and identified determinants influencing these domains to inform targeted capacity-building interventions and strengthen OH implementation. Methods: a cross-sectional, facility-based online survey was conducted from May to August 2025 among 332 governmental officers (MoHP: 112, MoAL: 115, MoE: 105) using a validated questionnaire adapted from previous KAP studies. The survey assessed sociodemographic characteristics, OH knowledge (10 questions), attitudes (12 questions on 5-point Likert scale), and practices (10 questions). Data were analyzed using descriptive statistics, independent samples t-tests, one-way Anova, multiple linear regression, and binary logistic regression using IBM SPSS statistics version 26. Results: participants demonstrated high knowledge of core OH principles, with 88.3% recognizing human-animal-environment interconnectedness and 87.0% understanding the need for multisectoral collaboration. However, critical gaps emerged regarding antimicrobial stewardship (only 44.3% answered correctly) and awareness of national OH programs (23.2% unaware). Attitudes were predominantly positive, with 64.2% strongly agreeing that oh would bring significant health benefits, though 51.2% identified lack of training as a barrier and 42.5% were uncertain about dedicated budgets. Practice engagement was moderate but uneven: 48.6% received workplace OH training, 37.3% participated in multisectoral meetings more than once, but only 19.9% and 26.8% were involved in AMR and food safety initiatives more than once, respectively. Multivariate regression revealed that organizational factors, entity affiliation, scope of role, and work related to OH were stronger predictors of KAP than individual demographics. Knowledge predicted attitudes (AOR = 3.044, p = .001), and attitudes strongly predicted practice (AOR = 1.764, p = .046), while knowledge did not directly predict practice, indicating that motivation and institutional support are more influential than cognitive understanding alone. Conclusion: Egyptian governmental officers possess strong foundational oh knowledge and positive attitudes, but these do not consistently translate into multisectoral practice, particularly in 1 AMR and food safety domains. Organizational characteristics, rather than personal demographics, are the primary drivers of KAP outcomes. Findings underscore the need for expanded training access, dedicated budgets with transparent accountability, formalized coordination mechanisms, enhanced cross-sectoral communication, and integration of oh responsibilities into job descriptions. Addressing these gaps is essential to operationalize Egypt’s OH strategic framework and strengthen health security at the human-animal-environment interface.